Biginelli Synthesis of Novel Dihydropyrimidinone Derivatives Containing Phthalimide Moiety - Mashooq A. Bhat; Mohamed A. Al-Omar; Ahmed M. Naglah; Abdullah Al-Dhfyan (Journal of Chemistry)
A new series of novel Biginelli compounds, 5-benzoyl-substituted phenyl-3,4-dihydropyrimidin-2(1H)-one-1H-isoindole-1,3(2H)-dione (1−10), were synthesized from enaminone, 2-{4-[(2E)-3-(dimethylamino)prop-2-enoyl]phenyl}-1H-isoindole-1,3(2H)-dione (IV), which was synthesized by refluxing 2-(4-acetylphenyl)-1H-isoindole-1,3(2H)-dione (III), with dimethylformamide-dimethylacetal (DMF-DMA) without solvent for 12 h. The compound 2-(4-acetylphenyl)-1H-isoindole-1,3(2H)-dione (III) was obtained by reacting phthalic anhydride (I) with para-aminoacetophenone (II) in glacial acetic acid for 2 h. The dihydropyrimidinone derivatives containing phthalimide moiety (1–10) were obtained by reacting enaminone, 2-{4-[(2E)-3-(dimethylamino) prop-2-enoyl] phenyl}-1H-isoindole-1,3(2H)-dione (IV), with urea and different substituted benzaldehydes in the presence of glacial acetic acid for 3 h. Simple and efficient method was employed to synthesize the dihydropyrimidinone derivatives containing phthalimide moiety. Structures of all the synthesized compounds were characterized by spectroscopic methods.